Knowledge Management practices in Malaysian Higher Learning Institutions: a review on selected cases - Hj. Yaakub, Muhamadul Bakir; Othman, Khatijah; Yousif, Ahmed F (2013)
This article underlines the fact that Malaysian Higher Learning Institutions are seriously geared in approaching its academic excellence status, becoming an international education hub attracting students from different parts of the world...